Perencanaan Titik Hydrant Pada Gudang PT. Putraduta Buanasentosa Menggunakan Standart NFPA 14 - Aditio Achmad Fauzi; Aditya Pradana; Dwi Novita Indirani; Wanda Ardhani Sulistyo; Dika Ayu Safitri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Awareness of potential hazards, risks of accidents, and the need for preventive measures is a must to create a safe and healthy working environment for all workers. The choice to implement a hydrant system is seen as an effective preventive measure in addressing potential fire risks, which are a major threat to the warehouse environment. Thus, this research planning has not only a purely academic purpose, but also seeks to make practical contributions to strengthening the application of the Principles of Occupational Safety and Health in the industrial sector. The planning research was done by jumping directly into the field and the data source was obtained from interviews with local authorities. This research describes the design of the hydrant system in order to be able and meet the safety standards set by the NPFA. The results of the conservation of the warehouse of PT. Putraduta Buanasentosa then the author was able to describe the building based on the construction of the building. The warehouse PT. Putraduta Buanasentoza requires hydrant boxes of 6 pieces. The water requirements for the fire protection system based on NFPA have been calculated by considering the building size as well as the risk of fire with hydrant 6 pieces and 1 hydrant pillar, requires 4800 liters of water/minute and to extinguish the fire in the event of a fire requires a time of 15 minutes where the required water requirements in 15 minutes is 72.000 litres of water.